The model approach to the choice of the vectors of socio-economic development of the territories - Каteryna Myhalova (Cхід, 2014)
Explores the nature and problematic aspects of sustainable socio-economic development (SED) territories at various levels of government (state, region, city). Structured typology types of territorial units on economic grounds. It is proved that for achievement of balance in the economy of a state, region, city effectively use the multi-level vector model of the national economy, which is designed to identify key vectors and composit-vectors, which will be planning, organization, financing and monitoring of effective socio-economic development in territorial units in the form of government (regional, interregional, sectoral, cross-sectoral) programmes. Proposed algorithm of realization of the multilevel vector model of the national economy.